Putting successful aging into context - Petery, Gigi; Iles, Lucinda; Parker, Sharon (Cambridge University Press, 2020)
In their excellent article, Kooij et al. (2020) introduce a self-regulatory model of successful aging at work. Their approach defines successful aging as “the proactive maintenance of, or adaptive recovery (from decline) to, high levels of ability and motivation to continue working among older workers” (p. 14). Their model proposes that personenvironment fit (P-F fit) is a proximal determinant of successful aging. When misfit occurs or is anticipated, individuals engage in a self-regulation process of proactive or adaptive goal engagement and disengagement strategies to restore or maintain P-E fit. Although they identify contextual factors, such as age bias and meso-level (job, team and organizational) factors, as antecedents of P-E fit and as catalysts for the self-regulation process, the model assumes these factors have their effects via individual processes. We believe this approach over-emphasises the role of individuals (i.e., the ‘person’), and understates the role of context (i.e., the ‘environment’), in achieving and maintaining P-E fit. In this article, we propose several modifications to the process model of successful aging at work (see Figure 1). We draw on Johns’ (2006) review of the role of context on organizational behaviour to describe the way environmental factors facilitate or constrain successful aging at work. First, we identify opportunity as a proximal determinant of successful aging at work (Path A in Figure 1) that explains the direct effects of context. Second, we argue that contextual factors (age bias and meso-level factors1) can moderate the misfit-self-regulation-fit process described in the model (Paths B1 to B3 in Figure 1). Finally, we use our proposed expanded model to suggest strategies that organizations can use to enhance employees’ successful aging at work.